Einige indogermanistische Anmerkungen zur mutmaßlichen Ableitungsgrundlage des Ortsnamens Leipzig: dem Flussnamen urgerm. *Līƀō‑ bzw. dem Gebietsnamen urgerm. *Līƀi̯a- (mit einem Exkurs zum Namen der Rhön und einem Anhang mit weiteren Überlegungen zum Namen der Elbe); Karlheinz Hengst zum 79. Geburtstag am 2.3.2013 - Bichlmeier, Harald (Namenkundliche Informationen, 2013)
The oldest forms of the place-name Leipzig, i.e. Libzi, Libiz vel sim., are now generally assumed to be Slavic, i.e. Old Sorabian derivatives of an older river-name, probably of Germanic origin. At the basis of this river-name is thought to be an enlarged root PIE *lei̯‑bh‑ ‘to flow, drip’. As the concept of root enlargement is somewhat problematic and should thus better be abandoned, it is claimed here – based on a recently published idea for the etymologization of the name of the river Elbe – that this assumed Germanic river-name is a derivative of an unenlarged root with the suffix PIE *‑bho‑. This suffix was used to form colour adjectives on the one hand and action nouns vel sim. on the other. Theoretical proto-forms of the river-name are PIE *h2lei̯H‑bho‑ or *h2liH‑bho‑ ‘making/being dirty/filthy’, PIE *lei̯H‑bho‑ or *liH‑bho‑ ‘nestling up against, winding itself’, PIE *lei̯H‑bho‑ or *liH‑bho‑ ‘pouring out’ (→ ‘flowing’?), PIE *lei̯h2‑bho‑ or *lih2‑bho‑ ‘dwindling, disappearing’, PIE *(s)lei̯H‑bho‑ or *(s)liH‑bho‑ ‘blue(ish)’, and PIE *(s)lei̯‑bho‑ ‘slippery, slimy’. A further theoretical possibility is the reconstruction as PIE *lei̯p-o‑ ‘sticky’ vel sim. (> ‘muddy’?). And finally, a reconstruction seems possible regarding the whole name not as a derivative, but as a compound with PIE *‑h2p-o‑ (the zero-grade of PIE *h2ep- ‘water’) as the second member. In this case, the same roots which form the bases of the derivatives are used as the first members of these compounds. All proposals show semantics acceptable for the formation of river-names. Thus no final decision between these proposals is possible.
Aus: http://nbn-resolving.de/urn:nbn:de:bsz:15-qucosa-150926
Gesehen am 05.05.2025
Keywords: Leipzig; Festschrift; Namenkunde; Ortsname